Online Learning Create a Creative Mind for Cheating or Knowledge Digging - Mohd Ruzani, Atiqah Liyana; Roslan, Nuralia Natasha; Abu Bakar, Norhaliza (Multidisciplinary Applied Research and Innovation, 2023)
In December 2019, the outbreak of new diseases known as SARS-Cov 1 or SARS-Cov 2, commonly known as the Corona Virus, has forced the transition of conventional education into a new learning phase, online education, to avoid spreading the diseases. This study observe the effect of online learning on the students' performance through the hypothetical items in the questionnaire,whether they obtain more knowledge or become more creative in cheating and scoring online exams . This study also investigates the meaning of cheating from the students' perspective, which can be different from the educator's perspective. The questionnaire consists of 3 sections: descriptive questions, cheating-related questions, and knowledge digging-related questions were distributed on the Google form to the intended respondents. The collected data are analysed using Excel software. Based on the data gathered, most students believe cheating is more beneficial than knowledge acquisition while participating in online education. However, avoiding these issues might seem impossible and consume a lot of time to create a new system. Therefore, instead of creating a brand-new system, the responsible parties should modernise the existing systems to be more secure and ensure the authenticity of students' work.